2010
DOI: 10.1002/art.27263
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvement in Churg‐Strauss syndrome

Abstract: Objective. Churg-Strauss syndrome (CSS) is a rare form of systemic vasculitis. Previous studies showing cardiac involvement in CSS patients were limited in the number of patients and were often based solely on clinical manifestations. The aim of the present study was to determine in detail the incidence of cardiac involvement in a large population of ambulatory CSS patients.Methods. Thirty-two consecutive patients with CSS in remission (mean ؎ SD duration of disease between diagnosis and enrollment 6.1 ؎ 5.8 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
121
2
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(143 citation statements)
references
References 46 publications
11
121
2
9
Order By: Relevance
“…Moreover, the accuracy of the assessment is dependent on the diagnostic methods used. For instance, we found that detailed cardiac evaluation revealed a 62% prevalence of cardiac involvement in our patients with eosinophilic GPA (previously Churg-Strauss), while only 26% had clinical symptoms 15 . Finally, whether a manifestation is caused by active vasculitis is not always evident nor can it always be proven.…”
Section: Patients Change Sizementioning
confidence: 67%
See 1 more Smart Citation
“…Moreover, the accuracy of the assessment is dependent on the diagnostic methods used. For instance, we found that detailed cardiac evaluation revealed a 62% prevalence of cardiac involvement in our patients with eosinophilic GPA (previously Churg-Strauss), while only 26% had clinical symptoms 15 . Finally, whether a manifestation is caused by active vasculitis is not always evident nor can it always be proven.…”
Section: Patients Change Sizementioning
confidence: 67%
“…To reduce CYC exposure, patients with early systemic disease were treated with a milder treatment regimen, i.e., MTX instead of CYC. In the NORAM (Nonrenal Wegener's Granulomatosis treated Alternatively with MTX) trial, MTX was not found to be inferior compared to CYC to induce remission 15 . However, results from the longterm followup are disappointing 16 .…”
Section: Which Treatment Is the Right Fit?mentioning
confidence: 95%
“…Although endomyocardial infiltration is the dominant condition, pericarditis, vasculitis, valvular heart defects, and abnormalities may also occur [52]. In addition, patients with EGPA have an increased risk of venous thromboembolic events, such as deep venous thrombosis and/or pulmonary embolism [53].…”
Section: Other Organs and Systemsmentioning
confidence: 99%
“…An observational study of 32 ambulatory CSS patients detected cardiac involvement in 62%. 2 In those with abnormal cardiac magnetic resonance imaging (MRI), echocardiography could detect cardiac involvement with 83% sensitivity and 80% specificity. In those with echocardiographic abnormalities, cardiac MRI detected cardiac involvement with 88% sensitivity, but only 72% specificity.…”
Section: Churg-strauss Syndrome: Remember Cardiac Complications Toomentioning
confidence: 99%